2023
DOI: 10.1590/1678-4685-gmb-2022-0190
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of OsNAC5 leads to up-regulation of OsNAC6 and changes rice (Oryza sativa L.) ionome

Abstract: NAC transcription factors are plant-specific proteins involved in many processes during the plant life cycle and responses to biotic and abiotic stresses. Previous studies have shown that stress-induced OsNAC5 from rice (Oryza sativa L.) is up-regulated by senescence and might be involved in control of iron (Fe) and zinc (Zn) concentrations in rice seeds. Aiming a better understanding of the role of OsNAC5 in rice plants, we investigated a mutant line carrying a T-DNA insertion in the promoter of OsNAC5, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…Transcripts of OsZIP2 and OsZIP3 have been postulated to exist in Zn-deficient root tissues . The increase of OsZIP1–3 expression that would have been predicted after 2 weeks of Zn deficiency in plants was not seen . OsZIP4 expression is increased when soil zinc levels are low.…”
Section: Approaches For Zn Biofortification In Ricementioning
confidence: 94%
See 3 more Smart Citations
“…Transcripts of OsZIP2 and OsZIP3 have been postulated to exist in Zn-deficient root tissues . The increase of OsZIP1–3 expression that would have been predicted after 2 weeks of Zn deficiency in plants was not seen . OsZIP4 expression is increased when soil zinc levels are low.…”
Section: Approaches For Zn Biofortification In Ricementioning
confidence: 94%
“…94 The increase of OsZIP1−3 expression that would have been predicted after 2 weeks of Zn deficiency in plants was not seen. 95 OsZIP4 expression is increased when soil zinc levels are low. Root apical meristem and vascular bundle phloem cells express OsZIP4 in Zndeficient plants.…”
Section: Molecular and Genetic Approaches For Zinc Fortifications 323...mentioning
confidence: 99%
See 2 more Smart Citations
“…S6A). Recent studies have indicated that overexpression of the OsNAC5 gene enhances the translocation of Fe and Zn from vegetative tissues to seeds (Wairich et al, 2023).…”
Section: Knockout Of Osnac5 Reduced CD Accumulation In Rice Grainmentioning
confidence: 99%